Stroke prevention in atrial fibrillation: Past, present and future. Comparing the guidelines and practical decision-making - Lip, Gregory; Freedman, Ben; De Caterina, Raffaele; Potpara, Tatjana S (Thrombosis and haemostasis, 2017)
Concepts and our approaches to stroke prevention in atrial fibrillation (AF) have changed markedly over the last decade. There has been an evolution over the approach to stroke and bleeding risk assessment, as well as new treatment options. An increasing awareness of AF has led to calls to improve the detection of and population screening for AF. Stroke and bleeding risk assessment continues to evolve, and the ongoing debate on balance between simplicity and practicality, against precision medicine will continue. In this review article, we provide an overview of past, present and the (likely) future concepts and approaches to stroke prevention in AF. We propose three simple steps (the Birmingham '3-step') that offers a practical management pathway to help streamline and simplify decision-making for stroke prevention in patients with AF.